2018
DOI: 10.1111/chd.12661
|View full text |Cite
|
Sign up to set email alerts
|

Exercise testing and spirometry as predictors of mortality in congenital heart disease: Contrasting Fontan physiology with repaired tetralogy of Fallot

Abstract: Variables most predictive of mortality in Fontan and TOF patients diverge but spirometry was abnormal and associated with mortality in both groups. When compared with age-matched controls, reduced FEV and FVC correlated most strongly with mortality in Fontan patients while VE/VCO slope correlated with mortality for TOF patients. These findings further support the importance of lung health in patients with complex congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…As for the relationship between the IPAQ survey results and both MRI and CPET parameters, we found a significant correlation between the IPAQ and peak VO 2 /Kg on multivariate analysis adjusted for age and gender, reflecting a possible positive effect of even a moderate level of physical activity on exercise capacity in the rToF population. The effectiveness of exercise training on improving peak VO 2 /Kg in cardiovascular diseases is currently well documented, even in CHD [47][48][49][50][51] yet there has been little discussion on prescribing regular physical activity to ToF patients to improve their long-term prognosis.…”
Section: Usefulness Of the Ipaq Survey In Rtof Patientsmentioning
confidence: 99%
“…As for the relationship between the IPAQ survey results and both MRI and CPET parameters, we found a significant correlation between the IPAQ and peak VO 2 /Kg on multivariate analysis adjusted for age and gender, reflecting a possible positive effect of even a moderate level of physical activity on exercise capacity in the rToF population. The effectiveness of exercise training on improving peak VO 2 /Kg in cardiovascular diseases is currently well documented, even in CHD [47][48][49][50][51] yet there has been little discussion on prescribing regular physical activity to ToF patients to improve their long-term prognosis.…”
Section: Usefulness Of the Ipaq Survey In Rtof Patientsmentioning
confidence: 99%
“…Four studies were rated as good 22,23,30,31 indicating a low risk of bias. Nine studies 24,28,[32][33][34][35][36][37][38] were considered "fair" with a lower internal validity in the view of the reviewers. The other studies [25][26][27]39 showed a higher risk of bias (e.g.…”
Section: Study Quality Ratingsmentioning
confidence: 99%
“…VO 2 peak is used as a means to measure cardiopulmonary function capacity and, in particular, to assess the severity of heart failure [32,33]. Heart failure is a leading cause for VT and SCD [34,35] [36,37]. In our study, .…”
Section: Discussionmentioning
confidence: 93%
“…Heart failure is a leading cause for VT and SCD [ 34 , 35 ] in acquired heart diseases; so, the correlation between O 2 peak and severe arrhythmia appears consistent. Previous studies in congenital heart diseases have linked decreased O 2 peak and increased E/ CO 2 slope during CPET with an increased rate of mortality or ventricular tachycardia in patients with tetralogy of Fallot [ 36 , 37 ]. In our study, E/ CO 2 slope did not show a clear correlation with the risk of severe arrhythmia during follow-up.…”
Section: Discussionmentioning
confidence: 99%